Visceral endoderm-restricted translation of Otx1 mediates recovery of Otx2 requirements for specification of anterior neural plate and normal gastrulation - Dario Acampora; Virginia Avantaggiato; Francesca Tuorto; Paola Briata; Giorgio Corte; Antonio Simeone (1998)
ABSTRACT Otx1 and Otx2, two murine homologs of the Drosophila orthodenticle (otd) gene, contribute to brain morphogenesis. In particular Otx1 null mice are viable and show spontaneous epileptic seizures and abnormalities affecting the dorsal telencephalic cortex. Otx2 null mice die early in development and fail in specification of the rostral neuroectoderm and proper gastrulation. In order to determine whether Otx1−/− and Otx2−/− highly divergent phenotypes reflect differences in temporal expression or biochemical activity of OTX1 and OTX2 proteins, the Otx2- coding sequence was replaced by a human Otx1 full-coding cDNA. Homozygous mutant embryos recovered anterior neural plate and proper gastrulation but failed to maintain forebrain-midbrain identities, displaying a headless phenotype from 9 days post coitum (d.p.c.) onwards. Unexpectedly, in spite of the RNA distribution in both visceral endoderm (VE) and epiblast, the hOTX1 protein was synthesized only in the VE. This VE-restricted translation was sufficient to recover Otx2 requirements for specification of the anterior neural plate and proper organization of the primitive streak, thus providing evidence that the difference between Otx1 and Otx2 null mice phenotypes originates from their divergent expression patterns. Moreover, our data lead us to hypothesize that the differential post-transcriptional control existing between VE and epiblast cells may potentially contribute to fundamental regulatory mechanisms required for head specification.